Effect analysis of unilateral deaf adults wearing bone-conduction hearing aids: A case report - Chenchen Xiang; Yi Wang; Xiaozhu Cao; Weiman Xv; Jing Liu; Nan Li; Lumeng Han; QIan Wang; Fei Ji (Journal of Otology, 2024)
The prevalence of unilateral deafness (SSD) or asymmetric hearing loss (AHL) among patients with hearing impairments ranges from 7.2% to 15.0%, indicating a relatively significant proportion. However, these individuals often overlook their hearing loss, resulting in delayed or inadequate treatment. This oversight can lead to a lack of binaural summation and squelch effect, as well as the head shadow effect, which can significantly impact their speech recognition and sound localization abilities, especially in noisy environments.Recently, a groundbreaking Sound Bite™ Pinyin® Bone Conduction Hearing Aid (HA) device has been has been introduced as a viable alternative to traditional percutaneous stimulation hearing assistance devices. This innovative device harnesses bone conduction technology to convey sound vibrations directly to the inner ear via the bones of the jaw and skull, effectively bypassing the air conduction pathway that is commonly compromised in individuals with hearing loss.This report details the evaluation and adjustment process of a HA device worn by a 31-year-old female patient who suffers from a congenital ossicular chain deformity in her right ear, while maintaining normal hearing in her left ear.The report comprehensively covers the hearing thresholds of the 31-year-old female patient on the day of fitting the hearing aid and one month later. It also presents assessments of the hearing aid's performance through the Abbreviated Profile of Hearing Aid Benefit (APHAB) questionnaire, conducted three days after adjustment, one month later, and one year later.Furthermore, the report details the evaluation of the patient's sound localization ability, comparing her performance before and after wearing the hearing aid device. Additionally, it includes measurements of her speech recognition ability for monosyllabic words and Yang Yang Ge words, which are specific tests in the Chinese language, conducted two years after the initial fitting of the hearing aid.The discovery that bone-anchored hearing devices can significantly enhance hearing thresholds in patients with unilateral conductive hearing loss represents a significant milestone. These devices not only improve speech recognition ability but also enhance sound localization in noisy environments. This improvement is accompanied by a high level of subjective satisfaction among patients, indicating a positive impact on their overall quality of life.